(3CKQ GdSjGSI GdSYQjI Ydi HYV GdeMGUjd GdESJQGJjLjI ai eUQs - (3GdHWQGf, eMSf eMehO(B.s (2003)
(3hGLg GdGbJUGO Gdbhej GdeUQj YbH GdfUa GdKGfj ef GdKeGfjfGJ JZjQGJ EbJUGOjI ef NdGd EfJgGL GdOhdI SjGSI GdEUdGM GdEbJUGOj , HGdCJaGb eY UfOhb GdfbO GdOhdj hGGdHfc GdOhdj ddEfTGA hGdJYejQ HgOa EUdGM GdYLR ai GdehGRfI GdYGeI ddOhdI hJMSjf GdNdd ai ejRGf GdeOahYGJ hGdejRGf GdJLGQj(B.s
(3jMJhj Ydi eQGLY(B.s
(3edNU HGddZI GdGfLdjRjI(B.s
1
Keywords: (3GdeMGUjds -- (3CbJUGOjGJs